Credit Markets, Property Rights, and the Commons - Noack, Frederik; Costello, Christopher (Journal of Political Economy, 2024)
Credit markets and property rights are fundamental for modern economies, but their implications for the commons are unknown. Using a dynamic model of competitive resource extraction, we show that improving property right security unambiguously increases conservation incentives, but the effect of credit markets on resource extraction effort hinges on the security of property rights. We test these predictions using data on global fisheries, credit markets, and the largest ever marine property rights assignment. We find that property right security reduces resource extraction and that credit market development increases resource extraction under insecure property rights but reduces resource extraction under secure property rights.